Adaptive resource allocation scheme for uplinks in IEEE 802.16m systems / Nurul Huda Mat Tahir - Nurul Huda, Mat Tahir (2013)
IEEE802.16m is a new standard for mobile WiMAX. It is expected to be the next 4G technology of wireless LAN offering high speed data rate and larger coverage area. Therefore to meet the requirements specified by IMT-advance (International Mobile Telecommunication Advance) a few amendments have been made from the earlier version of the standard. This thesis proposes a scheduler for uplink service and adapting the requirements outlined by the standard which includes the new advance air interface and an additional service class called aGPS. Dealing with scheduling Quality of Service (QoS) is still a scarce matter. To meet the QoS requirements, our scheduler uses a minimum group allocation where services that have QoS restriction will be put in this group. Only the remaining bandwidth will be distributed fairly using our enhanced deficit round robin (EDRR). EDRR gives variable effects on different types of user channel condition. To observe the performance, the proposed method is compared against deficit round robin (DRR). If the users are experiencing different channel conditions, DRR seems to be the best way of distributing the resources. However, when the users are having an identical channel condition, the method used by DRR in distributing the same amount of quantum number to all users will result in more packet drop for users with larger queues. Therefore DRR needs to be modified to not just considering the physical condition but also the state of user request. Thus the idea of EDRR is that the users with bulk data will have more chances to be mapped into an OFDMA frame. Since we do not want to violate the right of having more bandwidth for the users with the better channel quality, this method will only apply to those that having the same channel condition. The results show EDRR performs well than DRR by reducing the amount of packet drop.